Mediação e conciliação na sistemática processual brasileira: uma análise da autonomia da vontade à luz da legitimidade democrática do Poder Judiciário - Araujo, Daniel Guedes de (2017)
In Brazil, the access to justice movement has rescaled overcoming the formal validity of the law, seeking to promote a new function of institutions focused on the realization of the dignity of the human person. In the sphere of jurisdictional action, a new orientation towards the realization of constitutional values has been put in counterpoint to the legal-procedural structure, established with the Code of Civil Procedure of 1973, founded on the culture of litigation prioritized patrimonial and procedural ideology. Concerned with the demands of the citizens - and after a few years of preparation - the Brazilian legislator finally created a new structure of procedure and process with the edition of Law 13,105 of March 16, 2015, whose validity began in March 2016. The culture of peace and cooperation was appropriated in this new procedural structure. In this sense, the mediation was inserted in the CPC / 2015, which has as main characteristic the voluntariness. Conceptually, the defining voluntariness of mediation must be observed from the beginning of the procedure to the choice of the rules that should guide it, as well as, of course, the terms according to which, eventually, the agreement between the parties will be carried out. It happens that the new system adopted by the CPC / 2015 compromises the voluntariness, since it makes mandatory the submission to the conciliation or mediation hearing, independently of the own will, if the other party in the process demonstrates interest in submitting to that audience. Because of this innovation, the research problem arises: the introduction of a mandatory conciliation or mediation hearing by CPC / 2015, as a condition of procedurality that links the will of one party to the other, would confront the principles of autonomy of the will and freedom, corollaries of the mediation institute, in addition to clashing with the paradigm of access to justice (fair and adequate)? This evidence is intended to promote a critical analysis of the new procedural regulation (Law 13.105 of 2015) on conciliation or mediation procedures, as a condition of procedurality that submits its occurrence to the manifestation of the will of one of the parties, in accordance with the constitutional principles that inform the proceedings and, in particular, with the principles of the autonomy of the will and the freedom of the courts. To do so, the hypothetical-deductive approach is handled, considering that it will be based on the broader assumption of access to justice - fair and adequate, as a constitutional principle that informs the Brazilian Judiciary - through the analysis of the innovations brought by the CPC / 2015, in particular with regard to the conciliation procedure or mediation, which must occur, in most cases, independently of the adhesion of one of the parties, by subjecting one of them to the will of the other, in a manner compulsory.